Ultrasound is Not Useful as a Screening Tool for Dengue Fever - Parmar, Jitendra (Pol J Radiol, 2017)
BACKGROUND: Dengue fever is a tropical disease that is transmitted by female Aedes Aegypti mosquitos. Early diagnosis is necessary to reduce the mortality and morbidity associated with the disease. A combination of clinical, laboratory, and sonography findings can be potentially helpful in making an early diagnosis of dengue fever. There is paucity of literature on the use of ultrasound for dengue fever screening; hence, the primary objective of the study was to evaluate the utility of ultrasound as a screening tool in dengue fever. MATERIAL/METHODS: A total of 160 patients of suspected dengue fever were included in the study. They underwent ultrasound examinations in order to search for thickening of the gallbladder wall, pleural effusion, and ascites. On the basis of ultrasound findings, 65 cases were positive and 95 cases were negative for dengue fever. Serological tests were also used for diagnosing dengue fever, 93 cases were seropositive and 67 cases were seronegative. The ultrasonically diagnosed cases were compared with serologically diagnosed cases, and appropriate descriptive statistical analyses were applied. RESULTS: The ultrasound findings included gall bladder wall thickening in 66 patients (41.2%). The sensitivity, specificity, and positive predictive value of ultrasound in diagnosing dengue fever were 58%, 84%, and 83%, respectively. The negative predictive value and accuracy were 59% and 68.8%, respectively. CONCLUSIONS: The present study suggests that increased gall bladder wall thickness, pleural effusion, ascites, hepatomegaly, and splenomegaly are highly suggestive of dengue fever in clinically suspected cases. However, ultrasound should not be used as a screening tool, as negative ultrasound findings cannot rule out dengue fever due to the low sensitivity of this examination.